Efektivitas Penyuluhan Edukasi Seks Terhadap Pemahaman Tentang Perilaku Seks Bebas pada Anak Remaja Mesjid Al Muttaqin Kelurahan Tegal Sari Mandala III - Misri, Laily; Pasaribu, Robby Ade Syahputra; Habibi, Ahmad Ali; Masitah, Widya (Continuous Education: Journal of Science and Research, 2025)
Adolescents are a vulnerable age group, particularly susceptible to environmental influences, including risky sexual behaviors. A lack of understanding about healthy sexuality can lead teenagers to engage in premarital or unsafe sexual activities. This study aimed to enhance the effectiveness of sexual education counseling in increasing young people's understanding of free sexual behavior within the Tegal Salimandala III Almutakin Mosque community. A pre-experimental design was employed, utilizing a one-group pretest-posttest approach. The participants consisted of 23 mosque youths selected through purposive sampling. Data collection was carried out using questionnaires administered before and after the counseling session. The findings revealed a significant improvement in participants' knowledge following the intervention, as indicated by a rise in the average scores from the pre-test to the post-test. These findings indicate that sex education through counseling is effective in raising awareness among adolescents regarding the dangers and prevention of free sex behavior. This study recommends the continued implementation of sex education programs in mosque-based youth communities as a preventive measure against risky sexual behaviors.